Teacher Professionalism in Indonesia, Malaysia, and New Zealand - Kholis, Nur; Murwanti, Murwanti (TARBIYA: Journal of Education in Muslim Society, 2019)
AbstractIssues related to teacher professionalism may differ among countries. In Indonesia, the problems of teacher professionalism are connected to pre-service education and the lack of continuous professional development. In Malaysia, the major issues are concerned with teaching and management skills of teachers. In New Zealand, teachers face major issues related to work overload and the feeling of poor payment. Using a qualitative approach, this conceptual research paper discusses the issues of teacher professionalism and how the government takes roles in the continuing professional development of teachers in Indonesia, Malaysia and New Zealand. The research data was collected from the existing literature containing descriptions and discussions on the research topic and then analyzed using content analysis. The major findings of the study include that these three counties have issued laws, legislation, and regulations regarding the teacher profession. Then, teachers in the three countries are required to have the teacher’s standard competence embodied with a certificate. In addition,  before entering the classroom, all New Zealand teachers must have a certificate of teaching eligibility, while in Malaysia and Indonesia, the teacher certification is executed when teachers are already in the service. Finally, compared to Indonesia and Malaysia, New Zealand has a complete plan for improving teacher professionalism. The study concludes that the three countries put serious effort into improving the teaching profession. Similar research with more country samples would enrich the understanding of ways in which teacher professional development is conducted, thus providing valuable lessons for future reflections.AbstrakMasalah terkait dengan profesionalisme guru mungkin berbeda di setiap negara. Di Indonesia, masalah profesionalisme guru terkait dengan pendidikan pra-jabatan dan kurangnya pengembangan profesional berkelanjutan. Di Malaysia masalah utama berkaitan dengan keterampilan mengajar dan manajemen guru. Di Selandia Baru, guru menghadapi masalah besar terkait dengan kelebihan beban kerja dan persepsi terhadap rendahnya gaji guru.  Menggunakan pendekatan kualitatif, artikel penelitian konseptual ini membahas masalah profesionalisme guru dan bagaimana pemerintah berperan dalam pengembangan profesional guru berkelanjutan di Indonesia, Malaysia dan Selandia Baru. Data penelitian dikumpulkan dari literatur yang berisi deskripsi dan diskusi tentang topik penelitian, dan kemudian dianalisis menggunakan analisis konten. Temuan utama dari penelitian ini adalah bahwa tiga negara ini telah mengeluarkan undang-undang, peraturan perundang-undangan, dan peraturan tentang profesi guru. Kemudian, guru di tiga negara harus memiliki kompetensi standar guru yang diwujudkan dengan sertifikat. Selain itu, sebelum memasuki ruang kelas, semua guru Selandia Baru harus memiliki sertifikat kelayakan mengajar, sementara di Malaysia dan Indonesia sertifikasi guru dilaksanakan ketika guru sudah berada dalam layanan. Akhirnya, dibandingkan dengan Indonesia dan Malaysia, Selandia Baru memiliki rencana yang lebih lengkap dalam meningkatkan profesionalisme guru. Studi ini menyimpulkan bahwa ketiga negara melakukan upaya serius dalam meningkatkan profesi guru. Penelitian serupa dengan lebih banyak sampel negara akan memperkaya pemahaman tentang cara-cara di mana pengembangan profesional guru dilakukan, sehingga memberikan pelajaran berharga untuk refleksi di masa depan.How to Cite: Kholis, N., Murwanti. (2019).   Teacher Professionalism in Indonesia, Malaysia, and New Zealand. TARBIYA: Journal of Education in Muslim Society, 6(2), 179-195. doi:10.15408/tjems.v6i2. 11487.